المشكلات التي تواجه الإشراف التربوي من وجهة نظر كل من مديري المدارس الثانوية الحكومية ومعلميها في فلسطين محافظتي بيت لحم والخليل : دراسة حالة - شعيبات، محمد عوض; العبد، خالد فضل; شحاده، سونيا محمد (جامعة البحرين - مركز النشر العلمي, 2015)
This study aimed at exploring problems in the process of educational supervision from the points of view of public secondary school principals and teachers in Bethlehem and Hebron Districts. The study was conducted during the 2009 / 2010 academic year. A 44-item questionnaire covering five fields was distributed to a 227- teacher random sample and 75- principal random cluster sample after having determined its validity and reliability. Results showed that there were significant problems in the process of educational supervision. The results also showed that there were no significant differences among responses of the study samples (principals and teachers) due to the variables: sex, scientific qualification and length of experience. However, it showed that there were significant differences among the responses of the sample of the study due to the directorate variable.
هدفت هذه الدراسة إلى الكشف عن المشكلات التي تواجه الإشراف التربوي من وجهة نظر كل من مديري المدارس الثانوية الحكومية ومعلميها في فلسطين دراسة حالة، أجريت الدراسة على عينة عشوائية مكونة من (٧٥) مديرا، وعينة عنقودية عشوائية مكونة من (٢٢٧) معلما من محافظتي بيت لحم والخليل. وطبقت خلال العام 2009 /2010.باستخدام استبانة مكونة من (٤٤) فقرة موزعة على (٥) مجالات، تم التحقق من صدقها وثباتها، وأشارت نتائج الدراسة إلى وجود مشكلات تواجه عملية الإشراف التربوي بدرجة كبيرة، كما أشارت إلى عدم وجود فروق ذات دلالة إحصائية بين متوسطات استجابات عينة الدراسة تعزى لمتغيرات: الجنس، والمؤهل العلمي، وسنوات الخبرة، والمسمى الوظيفي. بينما أشارت إلى وجود فروق ذات دلالة إحصائية بين متوسطات استجابات عينة الدراسة تعزى لمتغير المحافظة.
Keywords: فلسطين -- المدارس الثانوية -- الإشراف التربوي -- بيت لحم -- الخليل -- المشكلات التربوية